Modeling and assessment of new urbanist principles in center neighborhoods in Kashan - Mohsen Shaterian; yones gholami; azam nazari (تحقیقات کاربردی علوم جغرافیایی)
The most important problem of the worn- ut context in urban is that these textures can not meet the needs of contemporary life. This can be of tissue due to the specific characteristics of a rare opportunity to play an effective role in sustainable development, one of the main strategies in this area can be a new urbanism approach. The aim of this study is to evaluate the principles of new urbanism is in the neighborhood of the central city of Kashan. The research method is analytical and is the main tool for data collection was a questionnaire. The sample size of 382 was calculated by the formula. To analyze the results of the questionnaire T-test through SPSS software is used for modeling equations using Amos software. The results suggest that indicators of modernity in the city of Kashan in central areas is not desirable, but a significant difference in terms of modern urban indicators in both new and old tissue there. The principles of modernism in town, the stand by weight of the total facade nodal regression 0.98 has most effective and the index of participation due to lack of poll officials on matters related to the principles of new urbanism is a minimal role in the neighborhood.